Viewing Vashti: As Victim, as Vilified, and as Venerated - Zucker, David J. (Women in Judaism, 2023)
Viewing the Biblical book of Esther’s Queen Vashti, chiefly through two lenses, traditional rabbinic commentaries, and how some contemporary authors, primarily poets writing in English, Vashti is seen as someone victimized, someone vilified, but also a woman to be venerated.